Fiqih Learning in Madrasah Ibtidaiyah Al-Ihsan Medari Sleman - Rafik Tri Hardian; Rakhmiyati Rakhmiyati (Kaunia: Integration and Interconnection Islam and Science Journal, 2020)
Learning is a interaction process between teacher and student. The teacher strives to create an environment that is conducive to the maximum learning process for students. In the learning process, there are several components, namely teachers, students, materials, curriculum, facilities and infrastructure, and evaluation. This study examines the learning of fiqh at the grade IV Madrasah Ibtidaiyah level. The purpose of this study was to determine how the processes of supporting and inhibiting factors in learning fiqh at Madrasah Ibtidaiyah Al-Ihsan Medari Sleman. The results of this study state that the process of learning fiqh at MI Al-Ihsan is the same as school there is generally that includes the initial, core, and final activities of learning. The material taught by the teacher is infaq and alms. In delivering the material, the teacher uses several methods including lectures, discussions and questions and answers.